Pengaruh Promosi dan Lokasi terhadap Minat Beli Pada Pizza Hut Karawang Cental Plaza Dimasa Pandemi Covid-19 - Hana Salsabila Kastanya; Anggi Pasca Arnu (Universitas Batanghari, 2022)
This study aims to examine and determine the effect of both partially and simultaneously Promotion and Location variables on Purchase Interest at Pizza Hut Karawang Central Plaza, using quantitative and technical methods of data analysis used is path analysis. The population in this study are prospective buyers and consumers of Pizza Hut Karawang Central Plaza and the sample is 100 respondents who are taken using a finite population with the slovin formula. The results showed that there was a correlation between promotion and location at the Pizza Hut restaurant, Karawang Central Plaza, which was 0.800 with a very strong correlation value. There is a partial effect of Promotion on Purchase Intention of 47.1%, this indicates that Promotion has a positive effect on Purchase Intention. There is a partial effect of Location on Purchase Intention of 32.8%, this indicates that Location has a positive effect on Purchase Intention. There is a simultaneous influence of Promotion and Location on Purchase Interest at Pizza Hut Restaurant Karawang Central Plaza of 57.7%, this shows that Promotion and Location have a contribution to Buying Interest of 57.7% while the remaining of 42.3 % is the contribution of other variables not examined in this study.